2015
DOI: 10.1371/journal.pcbi.1004455
|View full text |Cite
|
Sign up to set email alerts
|

Testing Foundations of Biological Scaling Theory Using Automated Measurements of Vascular Networks

Abstract: Scientists have long sought to understand how vascular networks supply blood and oxygen to cells throughout the body. Recent work focuses on principles that constrain how vessel size changes through branching generations from the aorta to capillaries and uses scaling exponents to quantify these changes. Prominent scaling theories predict that combinations of these exponents explain how metabolic, growth, and other biological rates vary with body size. Nevertheless, direct measurements of individual vessel segm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 56 publications
3
67
0
Order By: Relevance
“…This is not surprising given that different tissues and organs have different metabolic requirements. D r may vary within the vascular network with area-preserving branching closer to the heart and area-increasing branching slowing blood velocity in smaller vessels, but Newberry et al [22] find values for D r consistent with our predictions. Similarly, there is evidence that D w varies across hierarchical levels in computer chips [32].…”
Section: Discussion (A) Summary Of Scaling Predictionssupporting
confidence: 87%
See 2 more Smart Citations
“…This is not surprising given that different tissues and organs have different metabolic requirements. D r may vary within the vascular network with area-preserving branching closer to the heart and area-increasing branching slowing blood velocity in smaller vessels, but Newberry et al [22] find values for D r consistent with our predictions. Similarly, there is evidence that D w varies across hierarchical levels in computer chips [32].…”
Section: Discussion (A) Summary Of Scaling Predictionssupporting
confidence: 87%
“…The predicted value of D r between 2 and 3 is also consistent with the idea that the upper region of the network is area preserving with D r ¼ 2, while D r ¼ 3 in the lower region as proposed by West et al [5], and it is consistent with the empirical radius scaling reported in [22].…”
Section: (A) Mammallian Cardiovascular Networksupporting
confidence: 90%
See 1 more Smart Citation
“…Because vessel radii exhibit relatively little asymmetry and are consistent with existing models [29], we focus on asymmetries in vessel lengths and branching angles. Through the identification and investigation of these new, systematic patterns, an explanation might eventually be obtained for the mismatch between theoretical predictions from scaling theory and empirical data [9].…”
Section: Introductionmentioning
confidence: 79%
“…New RTN-based models (e.g., [84,[173][174][175][176]) or applications (e.g., [22,172,177]) continue to appear that have not sufficiently heeded the history of accumulating negative evidence against the assumptions, logic and predictions of previous RTN models.…”
Section: Resource-transport Modelsmentioning
confidence: 99%